Pengaruh Inflasi, BI-7 Day Reverse Repo Rate (BI7DRR), Dan Kurs Terhadap Nilai Aktiva Bersih (NAB) Reksadana Saham Syariah Dengan Pertumbuhan Ekonomi Sebagai Variable Moderasi - Kiki Wahyudi; Mellya Embun Baining; Khairiyani Khairiyani (JURNAL RISET MANAJEMEN (JURMA), 2023)
This study aims to prove that there is an influence between inflation, BI-7 Days Repo Rate, Exchange Rate on Net Asset Value (NAV) of Islamic stock mutual funds which is moderated by economic growth. By applying quantitative research methods and using time series secondary data from 2016 to 2021 and using a sampling technique, namely purposive sampling, as a determinant of the number of samples to be tested. Tests in this study use the help of IBM SPSS Statistics 22.0 software, which then data will be processed using descriptive analysis then multiple linear regression analysis.